2013
DOI: 10.14233/ajchem.2013.13601
|View full text |Cite
|
Sign up to set email alerts
|

Printing of Wool and Cotton Fabrics with Natural Dyes

Abstract: Natural dyes are the heritage of the history to human being. Although they were used for the colouration of goods from the ancient time, it is not common to use natural dyes commercially now. But at least in some special goods it is saving its popularities too. On the other hand, it can be foreseen that the demand on the ecological, natural and organic products in all consumable articles will make natural dyes popular again. Owing to this, it is important to continue the studies on the usability of natural dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
9
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 5 publications
6
9
1
1
Order By: Relevance
“…Relevant scientific literature is very limited, but research studies focusing on sourcing natural blue colorants for the printing of cotton are mainly approaching indigo, with results comparable with the ones obtained in this study, with L* values of 88,93 (Bahtiyari et al 2013).…”
Section: Figure 59 Color Specifications In Cielab Of the Printed Cotton Fabrics With C-phycocyaninsupporting
confidence: 84%
See 1 more Smart Citation
“…Relevant scientific literature is very limited, but research studies focusing on sourcing natural blue colorants for the printing of cotton are mainly approaching indigo, with results comparable with the ones obtained in this study, with L* values of 88,93 (Bahtiyari et al 2013).…”
Section: Figure 59 Color Specifications In Cielab Of the Printed Cotton Fabrics With C-phycocyaninsupporting
confidence: 84%
“…Printing is the process of application of colorant matter on the textile substrates with the support of binding agents and other auxiliaries, without considering the affinity of the colorant to the fiber, thus offering the possibility of application on all types of substrates (Bahtiyari et al 2013).…”
Section: Printing Processmentioning
confidence: 99%
“…Ragheb et al and Bahtiyari et al reported researches of wool and cotton printing with various natural dyes including walnut bark‐extracted dye, focusing on the pigment printing method. They confirmed that the natural dyes can be used in the pigment printing process without mordants, with binder, providing sufficient fastness …”
Section: Introductionmentioning
confidence: 71%
“…They are more environmentally friendly than manufactured colors are more biodegradable and usually contain a greater degree of environmental adaptability [3][4][5][6][7]. As mordant agents, metallic salts generate a connection among the dye molecules and the fiber by the formation of coordinating interactions [8].…”
Section: Introductionmentioning
confidence: 99%